Similar white matter but opposite grey matter changes in schizophrenia and high‐functioning autism. (22nd April 2016) - Katz, J.; d'Albis, M.‐A.; Boisgontier, J.; Poupon, C.; Mangin, J.‐F.; Guevara, P.; Duclap, D.; Hamdani, N.; Petit, J.; Monnet, D.; Le Corvoisier, P.; Leboyer, M.; et al.
Abstract : Objective: High‐functioning autism (HFA) and schizophrenia (SZ) are two of the main neurodevelopmental disorders, sharing several clinical dimensions and risk factors. Their exact relationship is poorly understood, and few studies have directly compared both disorders. Our aim was thus to directly compare neuroanatomy of HFA and SZ using a multimodal MRI design. Methods: We scanned 79 male adult subjects with 3T MRI (23 with HFA, 24 with SZ and 32 healthy controls, with similar non‐verbal IQ). We compared them using both diffusion‐based whole‐brain tractography and T1 voxel‐based morphometry. Results: HFA and SZ groups exhibited similar white matter alterations in the left fronto‐occipital inferior fasciculus with a decrease in generalized fractional anisotropy compared with controls. In grey matter, the HFA group demonstrated bilateral prefrontal and anterior cingulate increases in contrast with prefrontal and left temporal reductions in SZ. Conclusion: HFA and SZ may share common white matter deficits in long‐range connections involved in social functions, but opposite grey matter abnormalities in frontal regions that subserve complex cognitive functions. Our results are consistent with the fronto‐occipital underconnectivity theory of HFA and the altered connectivity hypothesis of SZ and suggest the existence of both associated and diametrical liabilities to these two conditions.